The KARAKTERISTIK FISIK DAN KIMIA BERAS COKLAT GERMINASI 3 JENIS VARIETAS PADI (MENTIK SUSU, CIHERANG, PANDAN WANGI) - Dwi Eva Nirmagustina (Jurnal Gizi dan Pangan Soedirman, 2021)
Brown rice has physical and sensory characteristics that are less favorable despite its high content of nutrition and phytochemical. The germination process is one way to improve and increase the acceptance of brown rice. The objective research was to determine germination time and varieties of brown rice on the physical and chemical characteristics of germinated brown rice. The research was conducted in RAL with 2 factors, germination time (24, 48, and 72 hours) and rice varieties (Mentik susu, Ciherang, and Pandan wangi). The data obtained were processed with analysis of variance to determine the effect of treatment on the parameters tested. If the effect is significant, then to determine the difference between treatments, a Tukey test is performed. Germination time of 24, 48, and 72 hours affected the color, germination, weight, dimensions of lenght, width, and thickness, bulk density, hydration capacity and swelling of germinated brown rice var. Mentik susu, Ciherang, and Pandan wangi. Germination time of 24, 48, 72 hours affected the chemical composition of BCG var. Mentik susu, Ciherang, and Pandan wangi. Based on observations of the physical and chemical characteristics of BCG var. Mentik susu, Ciherang, and Pandan wangi, germination time of 48 hours is recommended to do the germination with germination time of 48 hours compared to germination time of 24 and 72 hours.